Health Beliefs and Health Anxiety as Predictors of COVID-19 Health Behavior: Data from Serbia - Stanojević, Dragana Z.; Pavićević, Miljana S.; Živković , Tijana Lj.; Radović, Olivera B.; Jaredić, Biljana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The end of 2019 and the beginning of 2020 were marked by the appearance of the virus SARS-CoV-2, which led to a health crisis around the world. Health preventive behavior was highlighted as, at that time, the only form of prevention of the spread of the disease. Factors that will lead people to adhere to the recommended forms of behavior have become the subject of research in various scientific disciplines. The Model of Health Belief is one of the dominant frameworks for studying health behaviors, and thus behaviors related to COVID-19. Health anxiety and beliefs about illness and preventive behavior are the starting point for considering the level at which individuals adhere to the recommended measures. The main goal of this research was to examine a model in which health anxiety and health beliefs are predictors of preventive health behavior in relation to COVID-19. The sample consisted of 420 respondents, 66.3% of whom were women. They completed an online questionnaire comprising the following instruments: Short Health Anxiety Inventory, COVID-19 Health Belief Scale, and COVID-19 Health Behavior Scale with two subscales—Protection in Social Contacts and Hygiene. After controlling for effects of gender and presence of chronic disease, perceived benefit of preventive behavior and the observed barrier can predict protection in social contacts. Hygiene can be predicted by the perceived benefit of preventive behavior and the perceived barrier. Health anxiety has not been shown to be a significant predictor of health behavior. The paper discusses the theoretical and practical implications of the obtained results. The obtained results partially support the Model of Health Beliefs. In order to increase the degree to which individuals adhere to health behaviors, the benefits of preventive behaviors should be emphasized while the barriers should be reduced.
Keywords: health behavior; health anxiety; Health Belief Model